28th international papillomavirus conference & clinicaland public health workshops - JBDST (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Abstracts of research presented at the conference selected by edson natal Fedrizzi (Universidade Federal de Santa Catarina) e Mauro Romero Leal Passos (Universidade Federal Fluminense)We believe that this activity is a way to socialize and spread the knowledge to those who have not participated in important international scientific event.